261 Sport pre-participation health evaluation in elite athletes from a multisport club: proposal for a personalized protocol. (3rd March 2020) - Pi, Ramon; Garza, María Sanz de la; Grazioli, Gonzalo; Rodas, Gil; García, Manel; Sitges, Marta; Drobnic, Francheck
Abstract : Background: In 2009 the IOC published a Consensus Statement highlighting the value of periodic health evaluation in elite athletes. Objective: The aim of this study was to evaluate the prevalence of pathological findings, and the preventive value of the method used. Design: Retrospective epidemiological study. Setting and participants: A total of 2574 elite and professional athletes from Football Club Barcelona (FCB). FCB is a sports club with 13 different sports, 5 professional and 8 amateur. Interventions (or assessment of risk factors): Between 2008 and 2018, a total of 2574 athletes, with range from 12 to 35 years old, were evaluated through a personalized sport pre-participation health evaluation protocol (SPPHE) at the FCB Medical Department. Main outcome measurements: The protocol used was the ' Guía de la Revisión Médica del Futbol Club Barcelona' . The SPPHE examination consisted of basic medical information, anthropometric data, physical examination, spirometry, basal 12-lead electrocardiography, submaximal cardiovascular exercise testing, and cardiac echocardiography. Results: In 2574 SPPHE, we recorded 750 medical findings (29.1%); including 495 (19.2%) pathological findings, 255 (9.9%) minor abnormal findings, and 958 (37.2%) previous sports injuries. Specific treatment was necessary in 6 cardiovascular diseases. We found 3 endocrinological diseases (type 1e Diabetes Mellitus). Periodic follow-up was specified in all cases, although none prevented the athlete from competing. Conclusions: The SPPHE was effective in identifying a wide range of pathologies (66.3%) in elite athletes from this multisport club. This allow us to provide fast treatment and implement ad hoc strategic preventive programs. We found no alteration that affected the athlete's development or hindered them in reaching the highest level of competition.